Monitoring of Outdoor and Indoor Air Particulate Matter (PM10) at Buildings Located in An Industrial District - Al-Sahari, Mohammed; Al-Gheethi, Adel; Siti Zaidah, Siti Zaidah; Saphira, Radin Maya; Al Madhoun, Wesam; Anaam, Ahmed Abdulmalek (uthm, 2023)
Particulate matter (PM10) pollution has become a problem of significant impact in many countries and cities due to its dangerous effects on public health and environmental balance. The current study aims to monitor the indoor and outdoor PM10 concentrations of the buildings located next to an industrial area that releasing industrial fumes. Three buildings were selected to be investigated. Two factors were considered in the current study, including the outdoor PM10 and wind speed. Response surface methodology (RSM) design was used to identify the relationship between the outdoor and indoor PM10 concentration (I/O) through the ANOVA analysis (P<0.05). The obtained results of PM10 concentrations were showed an acceptable concentration (PM10.In.max= 34 µg.m-3, PM10.Out.max= 77 µg.m-3) compared to the Malaysian standard of Practice (DOSH) and RMAAQG (150 µg.m-3) for the selected areas. The investigation was showed a relationship between PM10.in, PM10.out, and the wind speed with a significant ANOVA factor (P < 0.05). The study findings are considered a knowledge contribution of the PM10 concentrations on the relationship of indoor and outdoor air quality for building surrounded by factories.